The Dormant Second Amendment: Exploring the Rise, Fall, and Potential Resurrection of Independent State Militias - Golden, Michael J. (2013)
The term “militia” is polarizing, misunderstood, misapplied, and generally difficult for modern Americans to digest. That is not surprising, given the depth and breadth of American militia history and militias’ substantial evolution over four centuries. Historically, militia simply refers to a broad-based civic duty to protect one’s fellow citizens from internal and external dangers and is not limited to activities involving firearms. Reestablishing militia’s true meaning and purpose—and reinvigorating independent state militias in the United States to effect that purpose—has the potential to address states’ emerging financial and security gaps and to produce multiple other significant benefits, including recalibrating federalism. This article suggests a method for how best to reinvigorate independent state militias, addresses the major critique against doing so, and initiates a real discussion about the future of state militias—an issue conspicuously underdeveloped in scholarship today